Dampak Berkepanjangan Bullying terhadap Mental Korban - Iklima Aulia; Tsabita Isyifa Ramadhani; M Fadlurrohman Al Husni; Sri Mulyeni (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Bullying is a form of aggressive behavior that is intentionally and repeatedly carried out, characterized by an imbalance of power between the perpetrator and the victim. This phenomenon is not limited to childhood and adolescence but may also produce long term effects that extend into adulthood, including among university students. This study aims to explore the long term impact of bullying on victims’ mental health, with a particular focus on students who have experienced bullying in the past. The study employed a descriptive qualitative method using a literature review approach. Data were obtained through a comprehensive analysis of scientific articles, national and international journals, and previous studies related to bullying and mental health. The findings show that victims of bullying face a higher risk of psychological problems, such as depression, anxiety, post traumatic stress disorder or PTSD, low self esteem, and difficulties in social interactions. These effects influence not only emotional well-being but also academic functioning, including reduced concentration, decreased learning motivation, and lower academic performance. In addition, prolonged psychological stress resulting from bullying may lead to physical problems, such as sleep disturbances and somatic complaints. Factors including limited social support, maladaptive coping strategies, and high intensity or prolonged exposure to bullying were found to intensify the negative impacts experienced by victims. Therefore, this study emphasizes the importance of comprehensive prevention and intervention efforts in higher education settings, such as the provision of accessible counseling services, the implementation of strict anti bullying policies, and the strengthening of social support systems to minimize the long-term mental health effects of bullying among university students.